Dampak Perpaduan Obat ARV pada Pasien HIV/AIDS ditinjau dari Kenaikan Jumlah Limfosit CD4+ di RSUD Dok II Kota Jayapura - Widiyanti, Mirna (Balai Penelitian dan Pengembangan Biomedis Papua, 2015)
The purpose of ARV is reducing the rate of transmission, reducing morbidity and mortalityassociated with HIV, restoring and maintaining the immune system and suppressing the viralreplication maximal. Dok II Hospital is one of the hospitals that provide care and ARV therapy forpatients HIV. The number of patients increasing each year, it is necessary to evaluate the success ofARV drugs on a regular basis in order to achieve optimal outcomes. One way of monitoring is tolook at the efficacy of a combination of ARV drugs on the immune response of the increase is theincrease in Lymphocyte CD4+ cell count. To determine the efficacy of ARV combination based onthe increase in CD4 cell counts of patients after 6-12 months of ARV treatment in Dok II Hospital in2011-2012. The study was an observational. Data were collected retrospectively on secondary datafrom medical records of patients who met the inclusion criteria. Data were analyzed by ANOVA. Sixobtained the drug combination gave good efficacy based on a significant increase in LymphocyteCD4+ cell counts in patients with HIV/AIDS who receive ARV drugs in combination II and V (pvalue = 0.002) and the combination of III and V (p value = 0.033) while for other combinationsbetween no significant difference. The sixth best combination ARV efficacy there are 2 that thecombination II and V combination.